Análise do custo de construção e manutenção de um prédio sustentável – o caso da empresa TEC - Schaab, Muriela (Universidade do Vale do Rio dos Sinos, 2014)
The search for sustainability in the companies has been discussed more and more, but the values not always seem attractive to the investors, who many times decide not to invest due to the lack of clarity on the values needed and the way the return is converted. In this sense, the current study has the general objective of evaluating the amount spent by TEC company in the construction of its second phase, which has the LEED Gold environmental certification and identify how much was dedicated to the sustainability itens, evaluating the time needed to obtain the return of the investment. To reach the aforementioned objective, this study makes use of applied research and case study. The data gathering technique relies on semi-structured interviews, document analysis and bibliographical research, and for the analysis of data, it is made use of quantitative and qualitative approaches. The study addresses the subject of sustainable constructions and investment decisions, as well as portraits the company's history and the reasons for its decision of investing on a sustainable building, presenting the costs with construction and investment on LEED with the analysis of its results. Finally, it is presented the conclusion of the study, where it is evidenced the financial return over a period considered to be satisfactory by the company, as well as the intangible aspects of the benefit of a green building.
Keywords: Construções sustentáveis; Certificação LEED; Decisões de Investimentos; Sustainable constructions; LEED Certification; Investment decisions